Silver(i)-mediated three-component annulation reaction of [60]fullerene, sulfonylhydrazones, and nitriles: leading to diverse disubstituted [60]fullerene-fused dihydropyrroles. Issue 5 (23rd November 2015) - Chao, Di; Liu, Tong-Xin; Ma, Nana; Zhang, Pengling; Fu, Zheng; Ma, Jinliang; Liu, Qingfeng; Zhang, Fengjin; Zhang, Zhiguo; Zhang, Guisheng
Abstract : A novel Ag(i )-mediated three-component annulation reaction of C60, sulfonylhydrazones, and nitriles is developed for the synthesis of diverse disubstituted C60 -fused dihydropyrroles. Abstract : A novel Ag(i )-induced three-component annulation reaction of [60]fullerene with sulfonylhydrazones and nitriles has been developed for the efficient synthesis of diverse disubstituted [60]fullerene-fused dihydropyrroles. The reaction exhibits a broad substrate scope and excellent functional-group tolerance, and also allows for the synthesis of fullerene-bound macromolecules.